The Rhopalidae (Hemiptera: Heteroptera) of Argentina - Pall, José Luis María (2012)
In Argentina, five genera and 34 species are recorded, in the subfamilies Rhopalinae and Serinethinae. Harmostes apicatus Stål; H. brevispinus Blöte; H. corazonus Distant; H. corizoides Jensen-Haarup; H. dorsalis Burmeister; H. gravidator (Fabricius); H. imitabilis Harris; H. insitivus Harris; H. marmoratus (Blanchard); H. minor (Spinola); H. parafraterculus Göllner-Scheiding; H. petulans Harris; H. procerus Berg; H. prolixus Stål; H. reflexus viscens (Dallas); H. serratus (Fabricius); H. signoreti Reed; Jadera aeola aeola (Dallas); J. choprai Göllner-Scheiding; J. decipiens Göllner-Scheiding; J. golbachi Göllner-Scheiding; J. haematoloma (Herrich-Schaefer); J. obscura (Westwood); J. parapectoralis Göllner-Scheiding; J. sanguinolenta (Fabricius); Niesthrea agnes Chopra; N. josei Göllner-Scheiding; N. pictipes (Stål); N. similis Chopra; N. vincentii (Westwood); Liorhyssus hyalinus (Fabricius); L. lineatoventris (Spinola); Xenogenus gracilis Berg; X. picturatum Berg; and X. extensum Distant. New locality records are given for Buenos Aires; Catamarca; Corrientes; Córdoba; Chaco; Entre Ríos; Jujuy; La Pampa; Mendoza; Misiones; Neuquén; Río Negro; Salta; San Juan; San Luis; Santiago del Estero; Tierra del Fuego. © 2012 Taylor and Francis Group, LLC.